Unpacking the impact of voucher schools: Evidence from Sweden - Karin Edmark; Iftikhar Hussain; Carla Haelermans (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
Research on voucher schools has mainly focused on whether students experience improved academic results in these schools and whether they generate competitive pressure for public schools. In this paper we focus instead on the role voucher schools might play in altering the menu of options available to students, for example with respect to vocational and academic tracks for adolescents. The setting for this paper is the period of rapid expansion of voucher schools in Sweden. Exploiting fine-grained geographical information on students' home location as well as variation in exposure across siblings, we uncover new evidence demonstrating that the introduction of voucher schools induces greater vocational education participation, and not simply a substitution of public for private vocational schools. In effect, voucher school penetration leads to a switch away from academic tracks, including academic science subjects, in favor of vocational options. We then assess the impact on medium- and long-term outcomes. The results demonstrate that voucher school penetration has a negative impact on the probability that the highest qualification is in a STEM subject by age 30. The results also reveal a negative impact on long-term labor market outcomes.
Keywords: H44; I21; I26; I28; 330; Private provision; independent schools; voucher school reform; vocational education; upper secondary education